Identification of Most Popular Musical Genres and their Influence Factors - Araujo, Carlos V.S.; Nakamura, Eduardo F. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Rap surpassed Rock as the most popular musical genre in the United States, according Nielsen Music. Understanding how this process occurred is of paramount importance for researches on prediction of musical success. Analyzing data from Billboard Year End Hot 100 rankings, we were able to identify that outstanding artists, such as Beatles and Mariah Carey, and movements, like New Wave and Trap, are the major factors influencing the success of a particular genre. Plus, we noticed that Pop Music is more inclined to be in the top spot.